Estados psicodélicos e sono no cérebro do rato: estudos comportamentais, eletrofisiológicos e moleculares - Souza, Annie da Costa (2020)
Classic psychedelics are substances known for altering consciousness. Its psychoactive effect is dependent on 5-HT2A and 5-HT1A serotonergic receptors, but due to the long prohibition of these drugs, little is known about their electrophysiological effects on the brain. In the current work I set out to investigate the effects of 5-MeO-DMT (DMT) and d-LSD, two potent serotonergic agonists, on the local field potentials (LFP) recorded from the hippocampus and prefrontal cortex of rats. Typical behavioral alterations ~15 min after drug injection were observed, such as increased locomotion, space occupancy, and the occurrence of stereotyped behaviors (wet-dog shake, uncoordinated gaiting etc). Similar to previous results, LFP alterations were detected in prefrontal cortical areas (PFC), as well as in the hippocampus (HP). The power in the theta (5-12 Hz) and gamma band (30-100 Hz) decreased in the two areas within the first 30 min after (i.p. and i.c.v.) DMT injection for all experiments, except for the highest dose of DMT (i.c.v.) in the PFC. Likewise, we found a similar result for d-LSD in the long-term analysis, there was a decrease in the gamma power after ~4h30min after d-LSD (i.p.) injection. Moreover, coherence analysis revealed that DMT (i.p.) increased the coherence between HP and PFC in the delta and gamma range. Next, we assessed how similar the changes caused by classic psychedelics are to the changes observed across the sleep-wake cycle. State map analysis revealed that both substances promoted a shift in the spectral profile typical of waking (WK) towards that of slow-wave sleep (SWS) or intermediated sleep (IS)/REM. Although animals remain awake after being treated with psychedelics, it is not a normal WK in terms of the LFP spectral profile. While some of the results obtained corroborate previous studies (e.g., the decrease in gamma power in the PFC), we also found divergent results, such as the decrease in PFC theta power. Altogether, the results are novel and promote a better understanding of the neurophysiological alterations caused by classic hallucinogens. The second chapter of this thesis is dedicated to the investigation of the cognitive role of the distinct sleep stages in terms of the molecular (and electrophysiological) correlates. Sleep plays an important role in memory consolidation and cognition, however little is known on the molecular mechanism that underlies this function, and which dynamic it would have across the different sleep stages (SWS and REM sleep). In previous works, we have demonstrated that phosphorylated CaMKIIα, a kinase protein related to synaptic plasticity, and CaMKII-dependent immediate-early gene (IEG), zif-268, are down-regulated during SWS and up-regulated during REM sleep in the HP of rats exposed to novelty in the previous waking. That IEG induction is initiated in the HP and is gradually transferred to the somatosensory cortex (S1). We hypothesized that the SWS and REM sleep play distinct roles in memory processing during sleep and that the phosphoproteomic profiles are as well distinct. More specifically, we screened the phosphorylated proteins of the S1 and the HP during both sleep stages of animals that were exposed (+) or not exposed (-) to novelty in the previous waking. We identified a total of 535 phosphoproteins in both HP (198) and S1 (337), and 90 were significantly modulated across the sleep cycle (S1=69; HP=21). The ontogenetic analysis revealed that the modulated proteins belong to several classes, for instance, cytoskeleton organization, RNA processing, calcium signalling pathways etc. Overall the results point that novelty-induced changes in protein phosphorylation levels are more pronounced in the S1 mainly during SWS (S1=23, HP=9, SWS+ x SWS-). Possibly, this upward/downward modulation could be related to the characteristics of the ‗up and down‘ states of the slow oscillations of SWS. A variety of functions were identified and a great part of that refers to the general functioning of the neurons, especially during SWS. During REM sleep there are fewer modulated proteins (S1=3, HP=3, REM+ x REM-). It is possible that novelty/stimuli would narrow the phosphorylation to more specific pathways related to sensory processing, mainly during REM sleep. We found that synaptic plasticity-related proteins are significantly modulated and some are correlated to SWS and intermediate sleep (IS) cortical spindle occurrence. For instance, Reelin, a protein that positively regulates synaptic morphogenesis, is upregulated during REM sleep compared to SWS of novelty exposed animals, and it is positively correlated to SWS and IS spindle count. Comparing the same groups (REM+ x SWS+) we found that CaCNA, a calcium voltage-dependent channel, is downregulated. The dephosphorylated CaCNA forms a complex (with Ca+2\Calcineurin) that regulates synaptic plasticity-related gene transcription. The functional analysis of proteins that are markers of experimental groups and spindles correlation analysis indicate that there is a concomitant enrichment of pathways related to synaptic reinforcement and weakening (e.g. activation of proteins kinases and phosphatases). Such an idea is corroborated by previous findings of our group and also by other recent evidence by other groups (e.g. REM sleep synaptic pruning and strengthening after motor learning). Our study indicates that SWS and REM sleep have different phosphorylation profiles, suggesting they have distinct and complementary roles in memory consolidation. Finally, our findings corroborate the theory of synaptic embossing during sleep, in which synapses are ‗reinforced‘ or ‗weakened‘.